A qualitative evaluation of a novel intervention using insight into tobacco industry tactics to prevent the uptake of smoking in school-aged children - Taylor, John; Taylor, Amy; Lewis, Sarah; McNeill, Ann; Britton, John; Jones, Laura L.; Bauld, Linda; Parrott, Steve; Wu, Qi; Szatkowski, Lisa; Bains, Manpreet (BioMed Central, 2016)
Background: Evidence from the US Truth campaign suggests that interventions focusing on tobacco industry tactics can be effective in preventing smoking uptake by children. Operation Smoke Storm is the first school-based intervention based on this premise and comprises three classroom sessions in which students act as secret agents uncovering tobacco industry tactics through videos, quizzes, discussions, and presentations. We report a qualitative evaluation of its acceptability. Methods: We conducted eight focus groups with 79 students aged 11-12 who participated in Operation Smoke Storm at two UK schools in Autumn 2013, and 20 interviews with teachers who delivered the intervention. These were digitally audio-recorded, transcribed verbatim and analysed using the framework method. Results: Students enjoyed the secret agent scenario and reported acquiring new knowledge about smoking and the tobacco industry, which seemed to strengthen their aversion to smoking. Teachers felt confident delivering the ‘off the shelf’ resource, although they would have welcomed more background information about the topic and guidance on steering discussions. Teachers highlighted a need for the resource to be flexible and not dependent on lesson length, teacher confidence, or expertise. Students and teachers endorsed the idea of developing a booster component for older students and supported the development of printed information complementing the resource to encourage parents to support their child not to smoke. Conclusions: These findings demonstrate that Operation Smoke Storm can be delivered by teachers to raise awareness about smoking-related issues. The ideas and issues raised are now being used to improve and extend the resource for further evaluation.